2010
DOI: 10.4103/0019-5154.60364
|View full text |Cite
|
Sign up to set email alerts
|

Lupus panniculitis as an initial manifestation of systemic lupus erythematosus

Abstract: In May, 2003, a 28-year-old female presented with large non-healing ulcers on face, trunk and limbs covered with black hemorrhagic crust. There were no other systemic manifestations. Diagnosis of lupus panniculitis was considered on clinical and histopathological grounds. The lesions healed completely, with scarring, with systemic corticosteroid, hydroxychloroquine and topical 2% mupirocin. She came again in November, 2005, with malar rash, joint pain, scarring alopecia of the scalp and albuminuria. Her ANA, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 5 publications
2
16
0
Order By: Relevance
“…The disease has a female to male ratio of 2:1, occurring predominantly in the age group of 20-60 years old. 5 The illness manifests itself as deep erythematous plaques and nodules, involving the trunk, breasts, buttocks, face, and proximal extremities. It does not commonly ulcerate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The disease has a female to male ratio of 2:1, occurring predominantly in the age group of 20-60 years old. 5 The illness manifests itself as deep erythematous plaques and nodules, involving the trunk, breasts, buttocks, face, and proximal extremities. It does not commonly ulcerate.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of lupus panniculitis is challenging because there are no specific indications or medication recommendations in the guidelines. 18 Antimalarial drugs are believed to bring improvement in mild cases of isolated lupus panniculitis. 19 Chloroquine in a dose of 200-250 mg a day and HCQ in a dose of 200-400 mg a day is typically recommended.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventy percent of LEP cases have been associated with DLE but two to five percent of cases have been accompanied by SLE [6,7]. Most cases of LEP have mild and fluctuant courses but up to 15% of cases could be able to progress to SLE and 50% of them have evidences of SLE, so LEP could be a preceding feature of systemic involvement and all patients should be followed up meticulously especially in cases with positive ANA [1,3,[6][7][8]. Arai, et al reported positive ANA in 95.2% of LEP cases [8].…”
Section: Discussionmentioning
confidence: 99%